Varietal Interventions and Their Significance in Rice-Based Cropping Systems of Drought-Prone Ecologies in Odisha - Nayak, Swati; Nath, Anirban; Hossain, S.K. Mosharaf; Singh, Varsa; Mohapatra, Subhasmita (Springer, 2025)
The eastern state of Odisha comprises of mostly smallholder farmers who remain extremely vulnerable to climatic stress including drought. Out of the last 41 episodes of natural calamities that hit the state in the last 50 years, 19 of these were severe droughts. This is aggravated by the fact that the state is dependent mostly on rainfed systems and only 38% of the cultivated area has coverage or access to some degree of irrigation. Securing sustainable rice-based cropping systems for smallholders in Odisha necessitates the availability of quality seeds for drought-tolerant rice varieties and short-duration non-paddy crops during the dry seasons. Through multi-year rigorous varietal on-farm testings (OFTs), several products have been identified and also scaled. Some of these are now highly popular and demanded varieties like Sahabhagi Dhan, DRR Dhan 42, CR Dhan 801. The yield performance in both stress and non-stress conditions, the grain quality and maturity duration and strategic demand creation efforts and supply have played an integrated role in large-scale adoption of these products. Going beyond stress-tolerant varieties, the recent development of national breeding pipelines around direct-seeded rice systems (DSRs) carries significant potential for drought-coping mechanisms. DSR as a system is directed towards saving of water and labour as well reducing greenhouse gas emissions. Under the breeding pipeline and market segment of DELS-I/R (Direct seeded early maturity long slender-irrigated/rainfed) many varieties have been tested through multi-location on-farm trials in various drought-prone and upland regions like Bargarh, Sambalpur. Newer early maturity varieties such as ADT 56, CO 56, MTU 1001, PR 126 and Tripura Hakuchuk 2 were extensively tested and compared with established checks like MTU 1010 and Sahbhagi Dhan. This requires a comprehensive evaluation and identification of a greater number of suitable products (varieties) for drought ecologies (not necessarily having drought tolerant genes, but tailored enough for drought escape through early maturity or low water responsiveness) and scaling those for impact. To enhance farm returns in post-kharif periods, the effectiveness of short-duration oilseeds (sunflower, sesame) and pulses (green gram, black gram, lentils, etc.) remains potential. The deployment of early maturing rice varieties ensures a second crop in otherwise dry-season fallow areas, contributing to sustainable agricultural practices. Finally, in order to ensure a steady supply of seeds for the rice and non-paddy crops, robust varietal and seed system interventions for drylands, carry potential for creating resilient model for combating the drought and its effects among the smallholders.